Evaluation Of Islamic Religious Education Learning Using The Artificial Intelligence -Based Deep Learning Approach - Kurnialoh, Nasri; Masrur, Imam; Fauziah, Syifa; Dia, Yousouf Ibrahim (LP2M IAIN kUDUS, 2025)
Infrastructure constraints, educator digital literacy, and ethics still need to be addressed through the evaluation of Islamic religious education (PAI) learning to assess students' cognitive, affective, and psychomotor competencies in improving conceptual understanding, critical thinking skills, and religious attitudes in PAI subjects. In the digital era, deep learning methodologies that include artificial intelligence (AI) strategies and technologies present opportunities to improve the effectiveness of evaluation. This study aims to evaluate How effective is the in-depth learning method in improving PAI learning outcomes, the data was analyzed using the qualitative literature approach of the Miles and Huberman model, by conducting Data reduction , data presentation, and conclusion drawing. The research results show that the integration of artificial intelligence-based deep learning results in more comprehensive and meaningful assessments for students, teachers, and educational institutions.